2021
DOI: 10.1029/2020ja028512
|View full text |Cite
|
Sign up to set email alerts
|

Average Ionospheric Electric Field Morphologies During Geomagnetic Storm Phases

Abstract: Geomagnetic storms are understood to be enhancements in the Earth's ring current (Akasofu & Chapman, 1961;Gonzalez et al., 1994). This westward-flowing current causes large-scale deviations in the Earth's magnetic field, such that they can be measured on the ground (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…There is a reason why we do not produce convection maps at a 3-hourly cadence: ionospheric convection can and usually does differ on much shorter timescales. For example, Walach and Grocott (2019) and Walach et al (2021) showed that during very active times, such as geomagnetic storms, ionospheric convection and in particularly the location of the HMB, varies on timescales of minutes and we thus do not advise to use a Kp parameterized HMB model. Walach and Grocott (2019) showed that during geomagnetic storms, which can also be described as extremely driven times, the HMB can move to latitudes as low as 40°, which SuperDARN radars prior to the mid-latitude expansion were not able to observe.…”
Section: The Importance Of Parametrizing the Hmbmentioning
confidence: 99%
“…There is a reason why we do not produce convection maps at a 3-hourly cadence: ionospheric convection can and usually does differ on much shorter timescales. For example, Walach and Grocott (2019) and Walach et al (2021) showed that during very active times, such as geomagnetic storms, ionospheric convection and in particularly the location of the HMB, varies on timescales of minutes and we thus do not advise to use a Kp parameterized HMB model. Walach and Grocott (2019) showed that during geomagnetic storms, which can also be described as extremely driven times, the HMB can move to latitudes as low as 40°, which SuperDARN radars prior to the mid-latitude expansion were not able to observe.…”
Section: The Importance Of Parametrizing the Hmbmentioning
confidence: 99%
“…There is a reason why we do not produce convection maps at a 3-hourly cadence: ionospheric convection can and usually does differ on much shorter timescales. For example, Walach and Grocott (2019) and Walach et al (2021) showed that during very active times, such as geomagnetic storms, ionospheric convection and in particularly the location of the HMB, varies on timescales of minutes and we thus do not advise to use a Kp parameterized HMB model. Walach and Grocott (2019) showed that during geomagnetic storms, which can also be described as extremely driven times, the HMB can move to latitudes as low as 40 • , which Super-DARN radars prior to the mid-latitude expansion were not able to observe.…”
Section: The Importance Of Parametrizing the Hmbmentioning
confidence: 99%
“…A follow up study will consider the full magnetic local time asymmetries as present in the current and many previous observations (Takahashi et al, 2016;Walach et al, 2021;Wharton et al, 2018). The formation of a plasmaspheric drainage plume on the dusk flank during storms has been shown to significantly alter the propagation characteristics of ULF waves (Degeling et al, 2018).…”
Section: Discussionmentioning
confidence: 81%